The beekeeper's daughter [compact disc, unabridged] - Montefiore, Santa, 1970- (Dreamscape Media, LLC, 2015)
The story of a mother and daughter searching for happiness, unaware of the secrets that bind them.--England, 1932: Grace Hamblin is growing up on the beautiful estate of the Marquess and Marchioness of Penselwood. The beekeeper's daughter, she knows her place; that is, until her father dies. Massachusetts, 1973: Grace's daughter Trixie Valentine is in love with an unsuitable young man. Jasper Duncliffe is wild and romantic, and in a band that might hit it big.